HUBUNGAN PENGGUNAAN KOMPUTER DENGAN KEJADIAN NYERI KEPALA TIPE TEGANG PADA PEKERJA - Suryanti Suryanti; Andi Ipaljri (Universitas Batam, 2019)
In the current era of globalization, humans always interact with technological developments. One result of the development of technology is the use of computers. The use of computers that are not under the ergonomic position causes effects on health, one of them is tension-type headaches. In the United States, 1-4% of patients coming to the Emergency Care Unit complain of headache, 90% of them are tension-type headaches. The proportion of migraine and other headache syndromes in the hospital. Harapan Bunda in 2011 and RS. Camatha Sahidya in Batam in Batam was 5% and 0.7% respectively. Whereas the incidence of tension headaches in 5 puskesmas in Batam in 2014 ranged from 0.5% - 1.3%. The proportion of tension headaches at the BIP Clinic in the January-April 2018 period is 1.5%. Tension-type headaches that occur continuously can cause barriers to daily activities. The purpose of this study is to determine the relationship of computer use with the incidence of tension-type headaches in workers. This research uses a descriptive-analytic method with a cross-sectional approach. The sampling technique is purposive sampling. Of 97 respondents who visited the clinical BIP that met the criteria, it was found that computer user respondents experienced tension-type headaches of 18 people (42.9%) and not tension-type headaches of 24 people (57.1%). Whereas the respondents who were not computer users experienced tension-type headaches of 10 people (18.2%), and non-tension-type headaches of 45 people (81.8%). Bivariate chi-square analysis showed that p = 0.008 (p <0.05). This means that Ha is accepted and H0 is rejected.